Penggunaan Diskresi dalam Penegakan Hukum oleh Kepolisian menurut Undang-Undang Nomor 2 Tahun 2002 tentang Kepolisian Negara Republik Indonesia - K, Roberts (Universitas Muhammadiyah Sumatera Barat, 2019)
The important role of the National Police as a law enforcer is very necessary. However, in meetings in the field, the police are faced with a decision in which he must choose an action taken outside the limits of his authority and outside the command of his leader. At certain times, a police officer must make the right decision or better known as